ANALISIS PENERAPAN PEMBELAJARAN DARING PADA SISWA KELAS V SDN 009 SAMARINDA ULU - Siska Oktaviani; Hairunnissa Hairunnissa (Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this study was to obtain information related to the online learning implementation for the 5th grade students of SDN 009 Samarinda Ulu during the Covid-19 pandemic. This research was a descriptive qualitative research. Respondents in this study were 9 people from SDN 009 Samarinda Ulu. The details of the 9 respondents in this study were 3 homeroom teachers of the 5th grade, 3 students and 3 parents. To maintain the confidentiality of the respondents’ identities, the researcher gave the names of the respondents R1, R2, R3, R4, R5, R6, R7, R8 and R9. The data techniques in this study were interviews and documentation. The interviews used in this study were interviews, interviews were conducted by telephone and WhatsApp. Documentation was used as supporting data for this research. The data analysis technique used in this study was the Miles and Huberman analysis technique with four stages, namely, data collection, data reduction, data presentation and conclusion; and data validity in the study used source triangulation. The results of this study indicated that the Covid-19 pandemic had a major impact on the learning process at SDN 009 Samarinda Ulu. Learning that was usually carried out through direct meeting turned into online learning; online learning was still ineffective due to confusion and unpreparedness of the teachers, students and parents in the implementation process and the lack of facilities and infrastructure.